Innovation to Control Cigarette Consumption and Stunting Through the Kabar Besti Program (Smoke and Stunting Free Families) - Heni Trisnowati; Isni, Khoiriyah; Ichtiarini Nurullita Santri; Zahra, Aini; Kurniasih, Esti; Nasir, Ardiansyah Jumaedi; Saputri, Melly Eka; Fajeria (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Cigarette consumption causes economic and health losses to smokers and their families. The main determinant of stunting in toddlers in Sleman Regency is cigarette consumption by family members. Aims: The research aims to develop innovations to control cigarette consumption and toddler stunting through the Kabar Besti (Keluarga Bebas Asap Rokok dan Bebas Stunting) or the Smoke and Stunting Free Families Program. Method: This research uses an action research approach which includes: 1) innovation development, 2) innovation dissemination, 3) program adoption, and 4) program evaluation. The research was conducted in Sumberan Hamlet, Candibinangun Village, Pakem District, Yogyakarta for 6 months, from August 2023 to January 2024. Result: The development of the Kabar Besti program was successfully initiated with the following phases: 1) needs assessment, namely gathering support, exposing the program, and looking for opportunities and challenges in implementing the program; 2) dissemination of innovation in the community, namely socialization of the program to hamlet heads, toddler Posyandu, youth groups, and youth and youth communities; measuring lung capacity and collecting data on cigarette consumption patterns in the community of fathers and teenagers; 3) program adoption is proven by a declaration of joint commitment to implementing the Kabar Besti program; 4) program evaluation: there was a decrease in the number of fathers who smoked from 70.1% before the intervention to 68.6% after the intervention. Conclusion: The Kabar Besti program has been successfully developed and proven to increase community and stakeholder commitment to controlling cigarette consumption and stunting.